Investigating the Effect of Vitamin D3 on Osseointegration of Dental Implants in Rabbits: An Experimental Pilot Study - Ekaterina Diachkova; Marina Petukhova; Yury Zhilkov; Polad Osmanov; Аlexey Pchelyakov; Svetlana Tarasenko; Silvio Taschieri; Gyuzel Runova; Valentin Fadeev; Svetlana Shalnova; Yana Khristidis; Victoria Zaborova; et al. (Wiley, 2024)
Conclusions: The study's results on the rabbit model in vivo confirmed the relationship between vitamin D3 and the process of osseointegration. This in vivo experiment can be the basis for future clinical study.